Pengaruh Kepemimpinan, Motivasi, dan Disiplin Kerja terhadap Kinerja Guru pada Yayasan Pendidikan An Nawawiyyah Tasikagung Rembang - Fredityas, Muhammad Inggit; Nurhidayati, Anik (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to prove the influence of leadership, motivation, and work discipline on teacher performance at the An Nawawiyyah Tasikagung Rembang Education Foundation. This study has a population of teachers at the An Nawawiyyah Tasikagung Rembang Education Foundation. The sampling technique uses saturated sample probability. The number of research respondents is forty. Multiple linear regression analysis is used to conduct this analysis. The results of the study indicate that the variables of leadership and work discipline have a positive but insignificant effect on teacher performance, but are not significant. The motivation variable has a significant positive effect on teacher performance. The Adjusted R Square value of this study is 0.465, or 46.5%, which indicates that the variability of the dependent variable, namely teacher performance, can be explained by independent variables such as leadership, motivation, and work discipline. Other independent variables, which are not explained in this study, cover 53.5% of the total variability